Effects of acute exercise on atherogenic lipids in untreated mild hypertensive patients - Čaparević Zorica; Kostić Nada; Ćelić Vera; Ćosić Zoran; Marina Đorđe; Ilić Sanja; Penčić Biljana (Vojnosanitetski Pregled)
Background/Aim. Exercise can positively influence risk factors associated with cardiovascular disease. The mechanisms by which exercise reduces atherogenic risk remain unknown. The aim of the present study was to investigate the effect of acute exercise (cardiopulmonary exercise cycle ergometer test) on atherogenic lipids in untreated mild hypertensive patients with or without hypercholesterolemia. This testing allows determination of exercise capacity, peak heart rate, and ventilation per minute (VE), peak oxygen uptake (pVO2) and exercise time (ET). Methods. The study group included 85 untreated mild hypertensive patients (according to VII Joint National Committee - JNC 7) divided into two subgroups: hypertensive hypercholesterolemic and hypertensive normocholesterolemic. The control group included 35 normotensive subjects divided into two subgroups: normotensive hypercholesterolemic and normotensive normocholesterolemic. Lipid profiles to determine were oxidized LDL (OxLDL) - a marker of oxidative stress, triglycerides, total cholesterol, LDL cholesterol, and HDL cholesterol, which were measured at rest and 30 minutes after the acute bout of cardiopulmonary exercise cycle ergometer test. Lipids profiles were measured by enzymatic methods. Oxidized LDL was determined by a commercially available sandwich ELISA (Mercodia AB, Uppsala, Sweden). C-reactive protein (CRP) was measured using chemiluminiscent methods (Immulite-DPC). Results. In our study OxLDL was significantly higher in hypertensive patients with atherogenic lipid profiles in basal condition, compared to the hypertensive patients without atherogenic lipid profiles and controls. There was a significant difference in CRP (p < 0.001) between hypercholesterolemics (hypertensive and normotensive) and normocholesterolemics (hypertensive and normotensive). We found increased OxLDL after exercise in both groups (hypertensive patients and normotensive), but only in the hypertensive hypercholesterolemic patients the difference was statistically significant (90.47 ± 15.31 vs. 105.94 ± 14.17 IU/L, p < 0.001). Systolic and diastolic blood pressures were significantly higher during exercise only in the hypertensive patients. There were significantly lower values of pVO2 only in hypertensive hypercholesterolemic patients. There were no significant differences between hypertensive and normotensive ones for ET and VE. In hypertensive ones we found after exercise a negative correlation between pVO2 and OxLDL (r = -0.473; p < 0.05), and pVO2 and CRP (r = -0.478; p < 0.05). We also found in normotensive normocholesterolemic patients a positive correlation between VE and systolic blood pressure (r = 0.420; p < 0.05), a negative correlation between VE and OxLDL (r = -0.421; p < 0.05), and VE and CRP (r = -0.561; p < 0.05). Conclusion. This study showed that acute exercise induces and increases oxidative stress only in untreated mild hypertensive patients with atherogenic lipid profiles. These results imply the need to normalize atherogenic lipid profile in untreated patients with mild hypertension in order to prevent an increased lipid peroxidation under acute exercise.